Formulation optimization and wound healing activity of Vitex trifolia L leaf extract loaded chitosan hydrogel film on hyperglycemic rats - Made Dwi Pradipta Wahyudi S; Dewa Ayu Arimurni; Komang Angelita Safira; Erika Yuda Colatama; Putu Bisma Duta Valenrika (Pharmaciana, 2022)
Decreased blood supply, high blood sugar level, and a possibility of bacterial infection in diabetic wounds pose risk for limb loss and mortality. Therefore, proper wound care is needed to improve the quality of life of diabetic patients. Vitex trifolia L (Legundi) extract is reported to have antibacterial and antioxidant activity that enhances cell proliferation and migration. The antimicrobial and hemostatic properties of chitosan film are viewed as an ideal material for enhancing wound healing. The film should retain its integrity and flexibility while used on the skin, therefore chitosan was combined with PVA and PVP K30 to improve its quality. The objectives of this study were to optimize the concentration of chitosan, PVP K30, and PVA towards the Legundi extract film properties, and to evaluate its wound healing activity on hyperglycemic mice using an incision wound model. In this study, the film’s compositions were optimized using a simplex lattice design, and the effects of its components on their characteristics, such as thickness, weight, folding endurance, swelling rate, and swelling index, were evaluated. BALB/c Mice were divided into three groups (Group I, Group II, Group III) which were treated with normal saline, placebo film, and Legundi film respectively once daily for 8 days. The result suggested that chitosan and PVA were responsible for affecting the film’s thickness, weight, and folding endurance, whilst PVP K30 was the dominant factor in increasing the swelling index and rate of the film. The optimum formula of Legundi extract films consists of 1.15 %(b/v) chitosan, 1.25 %(b/v) PVP K30, and 1.6 %(b/v) PVA. The animal treated with Legundi extract film have higher wound closure compared to the control and placebo group four days after wound incision (p<0.05). Thus, Legundi extract film was a potential dressing to treat a diabetic wound.